Moderasi Beragama di Kalangan Islam Puritan: Studi Kasus Jemaah LDII di Kediri - Huda, Moh. Qomarul; Styawati, Yuslia; Sulaeman, Mubaidi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This research aims to analyze the phenomenon of religious moderation that occurs in puritan Islam, focusing on a case study of Jemaah LDII (Lembaga Dakwah Islam Indonesia) in Sambiresik Village, Gampengrejo District, Kediri Regency. Purist Islam is known for its conservative and normative interpretation of religion, but this study reveals how the LDIIcongregation applies an inclusive and tolerant approach in their religious practice. The research method used was a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and content analysis of related documents. Data were analyzed using an inductive approach to identify patterns of behavior and views that emerged from the interviewees and data sources. The results showed that the Sambiresik Village LDIIcongregation has an inclusive approach to practicing religious teachings. Despite coming from a puritanical Islamic background, they practice tolerance towards other religious groups and advocate interfaith cooperation to advance the local community. This research also reveals the important role played by religious figures in promoting this inclusive attitude. In the context of Sambiresik Village, historical factors, religious education focusing on moderate understanding, and positive social interactions were identified as key drivers of this inclusive approach. However, challenges such as negative perceptions of other puritanical religious groups and external dynamics that could affect the stability of inclusiveness remain a concern. In conclusion, this study illustrates that religious moderation can occur among puritanical Islamists such as Jemaah LDII in Sambiresik Village. This shows the potential to build faith harmony amidst differences in beliefs. This study provides deep insight into how an inclusive approach to religious practice can be adopted and sustained in communities characterized by puritanical interpretations of religion.